Real-World Outcomes in Pre-Existing Neovascular Age-Related Macular Degeneration Subjects Undergoing Avacincaptad Therapy for Geographic Atrophy - Rush RB; Klein W; Rush SW; Reinauer RM (Clinical Ophthalmology)
Ryan B Rush,1– 3 Westin Klein,1,3 Sloan W Rush,1,2 Robert M Reinauer4 1Department of Ophthalmology, Panhandle Eye Group, Amarillo, TX, USA; 2Department of Surgery, Texas Tech University Health Science Center, Amarillo, TX, USA; 3Department of Ophthalmology, Southwest Retina Specialists, Amarillo, TX, USA; 4Department of Ophthalmology, New Vision Eye Center, Vero Beach, FL, USACorrespondence: Ryan B Rush, Department of Ophthalmology, Panhandle Eye Group, 7400 Fleming Blvd, Amarillo, TX, 79106, USA, Tel +1 806 351-1870, Email ryan.rush.md@gmail.comPurpose: To evaluate real-world outcomes in subjects with pre-existing neovascular age-related macular degeneration (AMD) undergoing intravitreal avacincaptad pegol (IVA) treatment for geographic atrophy (GA).Methods: This study was undertaken as a retrospective, case-controlled assessment of patients undergoing IVA treatment for GA from 2 community-based retina practices. Patients were separated into 1) a Study Group consisting of subjects with pre-existing neovascular AMD prior to initiation of IVA for GA, and 2) a Control Group consisting of AMD subjects without neovascularization prior to initiation of IVA for GA. Study and Control Group subjects had a baseline visual acuity of ≥ 20/200, a total GA lesion area of ≥ 1 mm2 and ≤ 17.5 mm2, and follow-up of 12-months following IVA commencement.Results: A total of 64 patients were analyzed. No significant differences in baseline characteristics were found between cohorts. The Study Group had a greater decrease in visual acuity [− 0.2 (− 0.24 to − 0.16) logMAR versus − 0.04 (− 0.06 to 0.02) logMAR; p< 0.0001], a greater increase in GA lesion growth [1.36 (1.09– 1.63) mm2 versus 0.52 (0.34– 0.70) mm2; p< 0.0001], and a higher incidence of exudation (p=0.0002) compared to the Control Group during the study period.Conclusion: This study suggests that patients undergoing IVA therapy for GA with pre-existing neovascular AMD have worse visual and anatomic outcomes at 12-months compared to a matched control group without pre-existing neovascularization; such patients therefore should be carefully counseled prior to initiation of IVA for the management of GA.Keywords: geographic atrophy, avacincaptad pegol, pre-existing neovascular age-related macular degeneration, complement inhibition, Izervay